UTERINE BLOOD FLOW DURING PERIPARTUM PERIOD IN BUFFALO AND ITS ASSOCIATION WITH SHEDDING OF PLACENTA - SINGH, N; GANDOTRA, VK; GHUMAN, SPS; DHINDSA, SS; BRAR, PS (The Indian Journal of Animal Reproduction, 2016)
Twenty-three normal calving buffalo were subjected to trans-rectal doppler sonography to assess the blood flow in ipsilateral (IpsiUA, side of pregnant horn) and contralateral (ContUA) uterine artery in relation to shedding of placenta within 6 h post-calving (n=18) or later (n=5). Doppler parameters viz. time average peak velocity  TAP), blood flow volume (BFV), and resistive (RI) and pulsatility index (PI) were measured immediately before the start of calving process, and at 30 min and 6 h post-calving. The values of TAP and BFV in the uterine artery recorded at the start of calving process invariably exhibited a decreasing trend by 30 min post-calving which continued till 6 h post-calving (p
Keywords: Buffalo; Calving; Doppler; Placenta; Uterine artery